Utilizing Multi-Criteria Decision-Making for Selecting the Optimal Cutting Fluid in the Turning Process under Various Operating Conditions - Patel, Devendra; Shrotriya, Abhishek; K Mehta, Pradeep; Patel, Gourav; Patidar, Lekhraj (Journal of Neonatal Surgery, 2025)
With the rapid advancement of computer-aided engineering tools, design methodologies have undergone significant transformation, particularly in the areas of computational design and optimization. This study focuses on selecting the most suitable cutting fluid for turning operations based on key machining parameters such as feed force, cutting force, radial force, and surface roughness. Multi-criteria decision-making techniques, specifically TOPSIS and VIKOR, are used to analyze and rank different cutting fluids. Parametric modeling is carried out using MS Excel, allowing for efficient evaluation by adjusting input variables without manual calculations. The experimental work involves machining mild steel using a single-point High-Speed Steel (HSS) cutting tool under varying cutting speeds, feed rates, and eco-friendly cutting fluids. The results are presented through graphical analysis to identify the most effective cutting fluid under specific conditions. Additionally, the study investigates the influence of coolant flow, spindle speed, feed, depth of cut, and cutting force on surface finish. Recognizing the critical role of cutting fluid in machining performance, this research proposes an optimization model to manufacturers in selecting the most appropriate cutting fluid for improved turning process outcomes